2016
DOI: 10.1038/srep20926
|View full text |Cite|
|
Sign up to set email alerts
|

Persistent activation of microglia and NADPH oxidase drive hippocampal dysfunction in experimental multiple sclerosis

Abstract: Cognitive impairment is common in multiple sclerosis (MS). Unfortunately, the synaptic and molecular mechanisms underlying MS-associated cognitive dysfunction are largely unknown. We explored the presence and the underlying mechanism of cognitive and synaptic hippocampal dysfunction during the remission phase of experimental MS. Experiments were performed in a chronic-relapsing experimental autoimmune encephalomyelitis (EAE) model of MS, after the resolution of motor deficits. Immunohistochemistry and patch-cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
73
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 73 publications
(78 citation statements)
references
References 41 publications
5
73
0
Order By: Relevance
“…Other research groups confirmed this evidence, suggesting a key role for this cytokine in synaptic plasticity defects observed during neuroinflammatory processes [58,66,[68][69][70]. However, endogenous IL-1β is normally expressed at low levels in control conditions, and it has been proposed to be essential for the physiological induction of hippocampal LTP and consolidation of memory [65,71].…”
Section: Microglia Neuroinflammation and Synaptic Plasticity: A Deepmentioning
confidence: 84%
See 2 more Smart Citations
“…Other research groups confirmed this evidence, suggesting a key role for this cytokine in synaptic plasticity defects observed during neuroinflammatory processes [58,66,[68][69][70]. However, endogenous IL-1β is normally expressed at low levels in control conditions, and it has been proposed to be essential for the physiological induction of hippocampal LTP and consolidation of memory [65,71].…”
Section: Microglia Neuroinflammation and Synaptic Plasticity: A Deepmentioning
confidence: 84%
“…In our laboratory, we found an impaired LTP induction in the hippocampal CA1 area both during the acute inflammatory peak phase of EAE [68] and the later remission phase [58]. As experimental model for MS, we induced EAE in Biozzi ABH mice, which are particularly prone to develop autoimmune responses, by the injection of syngeneic spinal cord homogenate [68].…”
Section: Hippocampal Synaptic Plasticity In Experimental Models Of Msmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that dentate gyrus morphological abnormalities have been described in MS (Gold et al, 2010;, and given the particular importance of the dentate gyrus for pattern separation, our results provide additional neuropsychological support for an early dentate gyrus disruption during the course of MS. This selective vulnerability of dentate granular neurons at the early stage of MS could be related to a differential pattern of microglial activation in the dentate gyrus compared to other hippocampal subfields (Di Filippo et al, 2016;Planche et al, 2017), but the exact underlying molecular mechanisms remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Several prior studies support that hippocampal dysfunction primarily mediates memory impairment in MS, both in the human disease (Sicotte et al, 2008;Dutta et al, 2011;Hulst et al, 2012;Planche et al, 2016) and in animal models such as experimental autoimmune encephalomyelitis (EAE) (Di Filippo et al, 2016;Nisticò et al, 2013;Planche et al, 2017). However, the precise neuropsychological and anatomical mechanisms leading to loss of episodic memory performance still remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%